Agriculture and climate change mitigation in the developing world - Scholes, Robert J.; Palm, Cheryl A.; Hickman, JE (2014)
Agricultural activities in the developing world directly contribute about 4.23 GtCO2eq/y to the current anthropogenic forcing of the global climate, and indirectly a further approximately 3.93GtCO2eq/y through forest clearing and degradation. Together they constitute a quarter of the total global climate forcing from all sources. Many proven agricultural practices and policies can reduce this impact on the global climate without compromising food production, or reduce the climate impact per unit of agricultural production. A reasonable target by 2030 for climate mitigation in developing world agriculture, taking into account the large difference between technical potentials and economically viable adoption rates and noting the equity issues relating to the mitigation activities in the developing world, is around 1.2 GtCO2eq/y for agriculture (~ 22% of projected unmitigated agricultural emissions by 2030) and 1.2 GtCO2eq/y for avoided and more climate-appropriate land use changes (~ 30% of current land use change related emissions).